The Long Arm of Prospective Childhood Income for Mature Adult Health in the United States. (December 2022) - Brady, David; Guerra, Christian; Kohler, Ulrich; Link, Bruce
Pioneering scholarship links retrospective childhood conditions to mature adult health. We distinctively provide critical evidence with prospective state-of-the-art measures of parent income observed multiple times during childhood in the 1970s to 1990s. Using the Panel Study of Income Dynamics, we analyze six health outcomes (self-rated health, heart attack, stroke, life-threatening chronic conditions, non-life-threatening chronic conditions, and psychological distress) among 40- to 65-year-olds. Parent relative income rank has statistically and substantively significant relationships with five of six outcomes. The relationships with heart attack, stroke, and life-threatening chronic conditions are particularly strong. Parent income rank performs slightly better than alternative prospective and retrospective measures. At the same time, we provide novel validation on which retrospective measures (i.e., father's education) perform almost as well as prospective measures. Furthermore, we inform several perennial debates about how relative versus absolute income and other measures of socioeconomic status and social class influence health.